Augmentation of a pyramid solar still performance using evacuated tubes and nanofluid: Experimental approach. (September 2019) - Sharshir, Swellam W.; Kandeal, A.W.; Ismail, M.; Abdelaziz, Gamal B.; Kabeel, A.E.; Yang, Nuo
Highlights: Investigated the effect of using evacuated tubes integrated with pyramid still. Conducted the effect of using evacuated tubes with copper oxide and carbon black integrated with pyramid still. Copper oxide and carbon black leads to improve the freshwater by about 27.85% and 33.59%. Maximum thermal efficiency was about 64.5% for the modified pyramid still with carbon black. Abstract: This paper presents an experimental approach of a new hybrid system of modified pyramid solar still combined with evacuated tubes and nanofluids for high thermal performance. The current work compares between the performance and costs of three different units; one reference conventional solar still (CSS) and a couple of pyramid solar stills namely: conventional pyramid solar still (CPSS) and modified pyramid solar still (MPSS). The MPSS was integrated with evacuated tubes and, furtherly, nanofluids which are copper oxide (CuO) and carbon black (CB) nanomaterials with 1.5% wt. According to resulted data, the enhancement percentage in total freshwater was 4.77 and 26.6% in the case of MPSS over CPSS and CSS, respectively. Furthermore, the total freshwater was improved by about 27.85 and 54.48% in case of MPSS with copper oxide over CPSS and CSS. Finally, the enhancement percentage in total freshwater was 33.59 and 57.098% in case of MPSS with carbon black over CPSS and CSS, respectively. Moreover, the daily efficiency (ηd ) of MPSS reached 50% whereas it reached 61% and 64.5% in the case of MPSS with copper oxide and carbon black, respectively. On the other hand, ηd reached 48 and 30% for CPSS and CSS, respectively. Finally, the performed cost analysis shows that the proposed MPSS with nanofluids has economically reasonable with the offered optimal thermal performance.